FEATURES OF LEGAL REGULATION OF ECONOMIC ACTIVITY OF ECONOMIC ENTITIES OF THE PUBLIC SECTOR OF THE ECONOMY - Netska, Liubov; Tsezar, Anna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Goal: identifying the features of economic activity in the public sector of the economy and the shortcomings of its legal regulation; formation of proposals for improving the legislation on economic activity in the public sector of the economy. Research methods: general (theoretical and complex) and special research methods (system-functional, formal-logical, forecasting) have been utilized. Results: features of legal regulation of economic activity in the public sector of the economy are outlined, gaps in the legal regulation of the influence of state bodies - subjects of organizational and economic powers on economic activity, the negative consequences of the interference of subjects of organizational and economic powers in the activities of state corporations are analyzed, the lack of proper guarantees for the protection of public sector entities has been proven, conclusions were drawn about the bureaucratized procedures of business planning, on the limited opportunities of state corporations to carry out economic activities independently. Discussion: types of economic activity in the public sector of the economy and highlighting among them the priorities for the state, the need for legislative consolidation of organizational and economic powers of state bodies in the management of which are business entities, improving the organizational and legal status of entities engaged in economic activities in the public sector of the economy, features of economic and legal liability in cases of violations in the implementation of economic activities in the public sector of the economy, legal approaches to the development of ownership policy for especially important enterprises in the economy of Ukraine in order to increase the efficiency of their economic activities and achieve the goals.